Different corticosteroid induction regimens in children and young people with juvenile idiopathic arthritis: the SIRJIA mixed-methods feasibility study - Ashley P Jones; Dannii Clayton; Gloria Nkhoma; Frances C Sherratt; Matthew Peak; Simon R Stones; Louise Roper; Bridget Young; Flora McErlane; Tracy Moitt; Athimalaipet V Ramanan; Helen E Foster; et al. (Health Technology Assessment, 2020)
Background: In the UK, juvenile idiopathic arthritis is the most common inflammatory disorder in childhood, affecting 10 : 100,000 children and young people aged < 16 years each year, with a population prevalence of around 1 : 1000. Corticosteroids are commonly used to treat juvenile idiopathic arthritis; however, there is currently a lack of consensus as to which corticosteroid induction regimen should be used with various disease subtypes and severities of juvenile idiopathic arthritis. Objective: The main study objective was to determine the feasibility of conducting a randomised controlled trial to compare the different corticosteroid induction regimens in children and young people with juvenile idiopathic arthritis. Design: This was a mixed-methods study. Work packages included a literature review; qualitative interviews with children and young people with juvenile idiopathic arthritis and their families; a questionnaire survey and screening log to establish current UK practice; a consensus meeting with health-care professionals, children and young people with juvenile idiopathic arthritis, and their families to establish the primary outcome; a feasibility study to pilot data capture and to collect data for future sample size calculations; and a final consensus meeting to establish the final protocol. Setting: The setting was rheumatology clinics across the UK. Participants: Children, young people and their families who attended clinics and health-care professionals took part in this mixed-methods study. Interventions: This study observed methods of prescribing corticosteroids across the UK. Main outcome measures: The main study outcomes were the acceptability of a future trial for children, young people, their families and health-care professionals, and the feasibility of delivering such a trial. Results: Qualitative interviews identified differences in the views of children, young people and their families on a randomised controlled trial and potential barriers to recruitment. A total of 297 participants were screened from 13 centres in just less than 6 months. In practice, all routes of corticosteroid administration were used, and in all subtypes of juvenile idiopathic arthritis. Intra-articular corticosteroid injection was the most common treatment. The questionnaire surveys showed the varying clinical practice across the UK, but established intra-articular corticosteroids as the treatment control for a future trial. The primary outcome of choice for children, young people, their families and health-care professionals was the Juvenile Arthritis Disease Activity Score, 71-joint count. However, results from the feasibility study showed that, owing to missing blood test data, the clinical Juvenile Arthritis Disease Activity Score should be used. The Juvenile Arthritis Disease Activity Score, 71-joint count, and the clinical Juvenile Arthritis Disease Activity Score are composite disease activity scoring systems for juvenile arthritis. Two final trial protocols were established for a future randomised controlled trial. Limitations: Fewer clinics were included in this feasibility study than originally planned, limiting the ability to draw strong conclusions about these units to take part in future research. Conclusions: A definitive randomised controlled trial is likely to be feasible based on the findings from this study; however, important recommendations should be taken into account when planning such a trial. Future work: This mixed-methods study has laid down the foundations to develop the evidence base in this area and conducting a randomised control trial to compare different corticosteroid induction regimens in children and young people with juvenile idiopathic arthritis is likely to be feasible. Study registration: Current Controlled Trials ISRCTN16649996. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 24, No. 36. See the NIHR Journals Library website for further project information.